2008
DOI: 10.1073/pnas.0809662105
|View full text |Cite
|
Sign up to set email alerts
|

Comparing face patch systems in macaques and humans

Abstract: Face recognition is of central importance for primate social behavior. In both humans and macaques, the visual analysis of faces is supported by a set of specialized face areas. The precise organization of these areas and the correspondence between individual macaque and human face-selective areas are debated. Here, we examined the organization of face-selective regions across the temporal lobe in a large number of macaque and human subjects. Macaques showed 6 regions of face-selective cortex arranged in a ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
562
6
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 600 publications
(636 citation statements)
references
References 52 publications
56
562
6
1
Order By: Relevance
“…social anhedonia). The fusiform gyrus, which is included in the MOT and MT/PCC regions, is strongly implicated in face processing which is a crucial aspect of social cognition (Kanwisher et al, 1997;Kanwisher and Yovel, 2006;Tsao et al, 2008). This result is in line with studies showing that adolescents with 22q11DS who have higher levels of negative symptoms typically perform worse on facial recognition tasks (Schneider et al, 2015).…”
Section: Morphological Brain Changes Associated With Negative Symptomsupporting
confidence: 79%
“…social anhedonia). The fusiform gyrus, which is included in the MOT and MT/PCC regions, is strongly implicated in face processing which is a crucial aspect of social cognition (Kanwisher et al, 1997;Kanwisher and Yovel, 2006;Tsao et al, 2008). This result is in line with studies showing that adolescents with 22q11DS who have higher levels of negative symptoms typically perform worse on facial recognition tasks (Schneider et al, 2015).…”
Section: Morphological Brain Changes Associated With Negative Symptomsupporting
confidence: 79%
“…Moreover, the neural circuits mediating visual social perception are largely homologous in humans and rhesus macaques (46). Our baseline behavioral data show that faces capture attention in the rhesus macaque in much the same way as they do in humans (47)(48)(49).…”
Section: Discussionmentioning
confidence: 59%
“…Recent research has also shown a close anatomical correspondence in the cortical regions selective for faces between macaques and humans [30]. Functional neuroimaging studies have confirmed not only that monkeys have a small number of discrete face-selective regions similar in relative size to those in humans [41,42], but also that the great majority of neurons in at least one of these face-selective regions (one of the face patches in STS) are themselves face selective [43].…”
Section: Recent Developmentsmentioning
confidence: 86%
“…[28,29]; for a review, see [5]). It is probable that there are other regions in more anterior regions of the human brain that are responsive to face stimuli, similar to the 'face patches' that have been discovered in macaque monkeys [30,31].…”
Section: Models Of Face Processing and Its Neural Substratesmentioning
confidence: 99%